TRADISI KAWIN MAYIT DALAM PERSPEKTIF HAK ASASI MANUSIA MENURUT TEORI HANS KELSEN (Studi Kasus Kabupaten Sidoarjo) - Sholicha, Imatus; Atinal Husna; Shafira Rahma Dewi; Muhammad Jazil Rifqi (USRATUNA: Jurnal Hukum Keluarga Islam, 2024)
The tradition of people passed away marriage is a wedding ceremony performed in front of the deceased body of one of the parents of the bride or groom who has passed away before the wedding. This people passed away marriage occurs when the parents of one of the bride or groom have passed away before the scheduled wedding date or when the couple is already engaged. This study includes empirical research and uses a phenomenological approach. This article examines the tradition of mayit marriage from the perspective of human rights using Hans Kelsen's theory. According to Kelsen, human rights are fundamental rights that must be protected without exception, regardless of cultural or traditional contexts. This study uses qualitative data as its main material, including primary and secondary data. Secondary data was obtained through interviews. The results of this study indicate that the mayit marriage is performed in front of the deceased body of the parent. In the context of human rights, it is important to consider the freedom of consent, emotional well-being, and gender equality in marriage practices. The government and religious authorities need to work together with the community to ensure that cultural traditions are respected, but also ensure that marriage practices do not violate individual basic rights and meet national legal requirements. Article 18B of the 1945 Indonesian Constitution (Article 2) acknowledges customary law and traditional community rights. In Hans Kelsen's human rights theory, which emphasizes positive legal construction.